Development of Multiplication Board Media Using the ADDIE Model to Improve Elementary Students’ Mathematics Learning Outcomes - Zia Arfina Taufani; Sudarsri Lestari; Vina Rohmatul Ummah (Al-Qalam Institue, 2026)
This study aims to develop and examine the feasibility and effectiveness of multiplication board media in improving mathematics learning outcomes among third-grade students. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and pretest-posttest assessments. The subjects involved material and media experts as validators and third-grade students as research participants. Data analysis was conducted descriptively, while the effectiveness of the developed media was evaluated using the Wilcoxon Signed Rank Test and N-Gain analysis. The results showed that the multiplication board media achieved a feasibility score of 95% from material experts and 85% from media experts, indicating a highly feasible and feasible category, respectively. Student responses demonstrated a very positive perception, with scores ranging from 80% to 90%. The Wilcoxon test showed a significance value of <0.001, and the average N-Gain score of 0.6872 (68.72%) indicated a moderate level of effectiveness. This study implies that multiplication board media can serve as an innovative and practical learning tool to support conceptual understanding and improve students’ mathematics learning outcomes.